Education Through Nature (and With Nature) as the Source of a Child's Resilience: The Educational and Healing Context of a Forest - Anna Błasiak (Ignatianum University Press, 2022)
The objective of the article is to present the healing and educational properties of a forest in the context of the digital and consumerist reality of the 21st century and to discuss education for resilience as a specific kind of mental strength, inner power, and ability to cope with obstacles by using one's own resources and reaching for social support. The research question was formulated as follows: What is the role of education through nature (and with nature) - an important element of which is a forest - in developing and reinforcing resilience in children? The choice of subject is justified by the social and cultural changes, which force a person to face new challenges and expectations. The dynamics of those changes leaves the modern person little time to think about, try to understand, and give meaning to the new conditions of life. Resilience may be a construct that facilitates adaptation to the changing and fragile reality and it may be developed and reinforced through contact with nature, that is, in a forest. In terms of its methodological aspects, the article includes research of a theoretical nature. The author has carried out a synthetic and analytical review of selected books, as well as an analysis of the existing data related to the issue in question.